The Effect of RAP Paraphrasing Strategy and Semantic Map Strategy on Reading Comprehension - Yusti Elida; Resy Oktadela (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was a causal comperative design. The aims of this research are (1) to investigate whether there is any significant difference on students’ reading comprehension between using RAP Paraphrasing and Semantic Map strategy in comprehending reading text, (2) to determine which one is more effective of the two strategies. The research design used in this study was Pre-test and Post-test Comparison Group Design. The writer took the sample as cluster sampling. The total sample was 50 students. The form of the test were essay test. The research finding were: first the writer found that significant probabilities was higher than 0.05 (sig 0.05) in multiple comparison one way ANOVA. The level of significance of students’ reading comprehension post-test mean score between experimental class and experimental group II in sig (2-tailed) is 0.017 means that Ha is accepted. The second finding is thatthe value of sig (2-tailed) is 0.000 and it is lower than significant probabilities 5% (P 0.05. The third finding that the value of sig (2-tailed) is 0.00 and it is lower than significant probabilities. The fourth finding that the value of eta square is 0,74. it is higher than 0,20 (0,74 0,20). The value 0,74 is included in Moderate Effect (0,51 – 1,00). The result of the fifth hypothesis testing shows that Ha is accepted. The last finding, by using RAP Paraphrasing strategy gave better result than using Semantic Map strategy which can be proven from the result value of eta square is 0,74 and 0,71.